Classification of crucifer cultivars based on the life-history of diamondback moth (Plutella xylostella) - De Bortoli, Sergio A. [UNESP]; Vacari, Alessandra M. [UNESP]; Goulart, Roberto M. [UNESP]; Ferraudo, Antonio S. [UNESP]; Volpe, Haroldo X.L. [UNESP] (Taylor & Francis, 2013)
We compared different cultivars and hybrids of crucifers in relation to development and life-history of diamondback moth (Plutella xylostella) to classify the plants according to their resistance to the pest. The plants used were Manteiga da Geórgia kale, Bola de Neve cauliflower, Ramoso Piracicaba Precoce broccoli, Chato-de-quintal cabbage, and the hybrid cabbages Midori, TPC668, TPC308, and TPC681. We evaluated performance daily until the pupal stage. Pupae were assessed individually to determine the pupal weight, performance, and pupal period. We determined the sex ratio, fecundity, fertility, and longevity of the emerged adults and calculated their reproductive potential. Cabbage hybrids TPC668, TPC308, and TPC681 do not support the development and reproduction of the diamondback moth. These hybrids show a level of resistance that is similar to that found the commercially available hybrid Midori and cultivar Chato de Quintal, which are known to be resistant to the diamondback moth. This finding implies that the capitata (cabbage) cultivars are the most suitable for planting because they are more resistant to pest than the cultivar's moth, acephala (kale). © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: Brassica oleraceae; cultivar resistance; Plutella xylostella; reproductive potential; crop performance; cultivar; fecundity; fertility; hybrid; life history; longevity; moth; pest control; pest resistance; plant; sex ratio; Acephala; Brassica; Brassica oleracea; Brassica oleracea var. botrytis; Brassica oleracea var. capitata; Brassica oleracea var. italica; Brassicaceae; Capitata; Lepidoptera; Plutellidae